It is Time to Realize the Promise of the Digital Mental Health Transformation: Application for Population Mental Health - Jonathan Adler; Deryk Van Brunt (Journal of Medical Internet Research)
AbstractThe past 25 years have seen the explosion of digital health care—from 1s and 0s initially serving most researchers for accomplishing their work, to the creation of smartphones, mHealth, and more recently artificial intelligence. The revolution for digital mental health is no longer in its infancy, as new tools are created to address mental health, sometimes even undergoing evaluation for adoption and efficacy. In fact, a recent study reporting on National Health Interview Survey data (annually conducted by the National Center for Health Statistics) indicated that, in 2024, 40% of adults reporting serious psychological distress used a digital health tool, which has increased from 21% in 2017 and 10% in 2013. Given the widespread access to digital tools and the potential of digital mental health, it is time for a new paradigm of care to address the mental health crisis in the United States. Reactive care, consisting largely of medication and counseling provided to those already experiencing severe or debilitating symptoms of mental anguish, is not adequate to address the needs of 22.8% of the US population (>55 million people) experiencing symptoms of a mental illness, and the larger number of people with preclinical mental health concerns. A population mental health approach is needed that includes early identification, intervention, and prevention, in addition to reactive care.